2004
DOI: 10.1210/jc.2003-032054
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin Gene Polymorphisms in Men with Coronary Artery Disease

Abstract: Osteoprotegerin (OPG) antagonizes receptor activator of nuclear factor-kappaB ligand (RANKL), the principal regulator of osteoclasts. Of note, OPG-deficient mice display osteoporosis and arterial calcification. Recently, OPG gene polymorphisms have been associated with osteoporosis and early predictors of cardiovascular disease. In this study, we examined OPG gene polymorphisms in 468 men who had absence of coronary artery disease (CAD) or single-, double-, or triple-vessel disease on coronary angiography. Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 26 publications
5
80
2
1
Order By: Relevance
“…Another limitation is that we did not study the OPG vs. the RANKL polymorphism of the patients included in this study. The OPG polymorphism is known to be associated with cardiovascular disease [26,27]. Further, the OPG polymorphism carrier state may become a valuable molecular marker of the risk of CAD [28].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Another limitation is that we did not study the OPG vs. the RANKL polymorphism of the patients included in this study. The OPG polymorphism is known to be associated with cardiovascular disease [26,27]. Further, the OPG polymorphism carrier state may become a valuable molecular marker of the risk of CAD [28].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…OPG gene polymorphisms with increased risk for coronary artery disease and osteoporotic fracture were reported [22][23][24][25], and recently, RANKL gene polymorphisms have been studied relative to bone mineral density and osteoporotic fracture [24,26,27]. However, there has been no reported data on the association of cardiovascular system with RANKL gene polymorphisms.…”
Section: Measurements Of Bone Turnover Markers and Hormonesmentioning
confidence: 99%
“…Gene polymorphisms in KLOTHO, which encodes a hormone with anti-aging properties that is involved in phosphate regulation, were reported to be associated with bone mineral density and coronary artery disease in Asian population [34][35][36]. Polymorphisms in OPG gene, which is a decoy receptor for RANKL, were reported to be associated with osteoporosis and increased risk of coronary artery disease and vascular morphology [22,37]. In a study performed in the same study population as this study, no significant relationship was found between four OPG gene polymorphisms and aortic calcification or cardiovascular risk factors [27].…”
Section: The Differences In the Aortic Calcification According To Difmentioning
confidence: 99%
“…Serum OPG levels have shown to have prognostic value in heart failure after acute myocardial infarction as well as in patients affected by abdominal aortic aneurysm and peripheral artery disease (Karan et al, 2005;Ziegler et al, 2005). Remarkably, two OPG genetic polymorphisms have been associated with an increased risk of coronary artery disease in Caucasian men, and serum OPG levels correlated with one of these polymorphisms (Soufi et al, 2004). Thus, these studies strongly indicate that serum OPG levels frequently rise in clinical conditions that favor vascular dysfunction or atherosclerosis.…”
Section: Vascular Diseasesmentioning
confidence: 86%